2016
DOI: 10.1186/s12943-016-0494-6
|View full text |Cite|
|
Sign up to set email alerts
|

Aurora kinase targeting in lung cancer reduces KRAS-induced transformation

Abstract: BackgroundActivating mutations in KRAS are prevalent in lung cancer and have been causally linked to the oncogenic process. However, therapies targeted to oncogenic RAS have been ineffective to date and identification of KRAS targets that impinge on the oncogenic phenotype is warranted. Based on published studies showing that mitotic kinases Aurora A (AURKA) and B (AURKB) cooperate with oncogenic RAS to promote malignant transformation and that AURKA phosphorylates RAS effector pathway components, the aim of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 67 publications
1
32
2
Order By: Relevance
“…For the cap-dependent dual luciferase reporter assays, cells were transfected with 1 lg of a dual-renilla-fireflyluciferase pcDNA3-rLuc-PolioIRES-fLuc reporter (a kind gift from John Blenis, Harvard Medical School), to measure cap-dependent/cap-independent translation (Dos Santos et al, 2016). Cells were plated in six-well plates, transfected using Lipofectamine 2000 reagent (Life Technologies), and treated with MLN8237 for 24 h. The lysates were prepared in triplicate, and the dual luciferase reporter assay (Promega) was used following the manufacturer's protocol.…”
Section: Luciferase Reporter Assaymentioning
confidence: 99%
“…For the cap-dependent dual luciferase reporter assays, cells were transfected with 1 lg of a dual-renilla-fireflyluciferase pcDNA3-rLuc-PolioIRES-fLuc reporter (a kind gift from John Blenis, Harvard Medical School), to measure cap-dependent/cap-independent translation (Dos Santos et al, 2016). Cells were plated in six-well plates, transfected using Lipofectamine 2000 reagent (Life Technologies), and treated with MLN8237 for 24 h. The lysates were prepared in triplicate, and the dual luciferase reporter assay (Promega) was used following the manufacturer's protocol.…”
Section: Luciferase Reporter Assaymentioning
confidence: 99%
“…We used the b-galactosidase reporter for the pulse experiment, and the Katushka reporter for the pulse + chase experiment. We also found in Sirt1-Tg mice several downregulated protein kinases with pro-tumorigenic roles: Aurora kinase B (Aurkb); protein kinase C-iota (Prkci), and MAP-kinase activating death domain (Madd) [55][56][57]. During the pulse phase, we observed that genes involved in antioxidant defenses were upregulated in the Sirt1-Tg mice, such as several members of the glutathione S-transferase family, whose deletion has been found associated with poor prognosis in lung tumors [50], or Sod3, which has been shown to be downregulated in lung tumors [51] (Fig 4D), suggesting that Sirt1 overexpression is associated with stronger oxidative defense.…”
Section: Sirt1-tg Pneumocytes Display An Anti-tumorigenic Profile Durmentioning
confidence: 87%
“…The differentially expressed genes were grouped according to their function, and we focused our attention on the significantly altered genes between Sirt1-Tg and Sirt1-WT pneumocytes that were reported to play a role during tumorigenesis (red-marked bars in Fig EV4D and E). Interestingly, Aurkb has been shown to act as a target of K-Ras signaling, and its disruption reverted K-Ras-mediated tumorigenesis in lung cells [57]. Genes involved in carbohydrate and amino acid metabolism were also differentially regulated in Sirt1-Tg pneumocytes: increased glycogen phosphorylase (Pygm), that has been found decreased in lung tumors [52]; and decreased expression of the tumor inducers glutamine-fructose-6 phosphatase transaminase 1 (Gfpt1) [53] and hexokinase 2 (Hk2) [54].…”
Section: Sirt1-tg Pneumocytes Display An Anti-tumorigenic Profile Durmentioning
confidence: 99%
“…For example, breakpoint cluster region‐Abelson kinase (BCR‐ABL) promotes chronic myeloid leukemia (CML) cells proliferation via activating Aurora‐A and Aurora‐B kinases . Aurora‐A and Aurora‐B are also important targets of KRAS in lung cancer when targeting Aurora kinase reduces KRAS‐induced transformation . Thus, uncontrolled cell‐cycle progression is involved in Aurora‐A‐promoted tumorigenesis.…”
Section: Functions Of Aurora‐amentioning
confidence: 99%
“…42 Aurora-A and Aurora-B are also important targets of KRAS in lung cancer when targeting Aurora kinase reduces KRAS-induced transformation. 43 Thus, uncontrolled cell-cycle progression is involved in Aurora-A-promoted tumorigenesis.…”
Section: Proliferationmentioning
confidence: 99%